Psychometric Properties of Achievement Goal Constructs for Chinese Students - Zhao, Ningning; Zhai, Yanfang; Chen, Xiaohan; Li, Meiling; Li, Ping; Ye, Kunyu; Wen, Hongbo (Frontiers in Psychology, 2020)
Class is one of the special organizations in Chinese school. And special monitor and teachers contributed to the students’ achievement goal structure. The study aimed to examine the psychometric properties of perception of the teachers’ achievement goal structure constructs with 3,149 of Chinese student from grade 3 to grade 8. Firstly, the internal consistencies of the whole scale and subscales were low to marginal. Nine models were examined to check the constructs of the achievement goal structure (mastery, performance, performance–avoidance). It was showed that two factors structures fits well. Secondly, the multilevel confirmatory factor analysis proved that the achievement goal structure existed at the same time in the class level and in the student level after controlling for the demographic variables. The present study explored the different constructs for the students with from grade 3 to grade 8. Our finding supported that the achievement goal structure were different for the students with different culture.